Improving the Reliability of Weather and Climate Services in Yemen - Sieghart, Lia Carol (World Bank, Washington, DC, 2013)
The Republic of Yemen, situated on the southern end of the Arabian Peninsula, is one of the poorest countries in the world. In addition to significant development challenges, Yemen is particularly vulnerable to climate change. Rainfall is erratic and variable, a situation made worse by high evapotranspiration rates. Sustainable social and economic development in Yemen depends on knowledge of climate variability and change, and reliable and actionable meteorological and hydrological forecasts and warnings. Upgrading weather, climate and water information will reduce vulnerabilities to natural hazards and increase food and water security. Yemen is particularly reliant on its natural resources outside the extractive industries. Agriculture plays a leading role in Yemen's economy and employs more than half of the labor force. Through the Pilot Program for Climate Resilience (PPCR), Yemen aims to better manage water resources, increasing agricultural productivity and reducing the risk of climate-sensitive diseases. This will be done by improving the monitoring and assessment of climate variability and change and providing targeted and reliable information for decision making.